Modelling of consumer confidence generating, based on cluster analysis - Дьячкова, Ольга Владимировна (Technology audit and production reserves, 2015)
This article presents the application of cluster analysis to marketing strategy development for company products promotion. The objectives of this work are consumers segmentation, identification of internal patterns and making recommendations for each target group. The mechanism of consumers segmentation based on k-means clustering method. Validation of method choice, splitting the initial data on training and test sets are described, along with choice of input and output fields for iterative process of clustering. For each of resulting clusters, its features are analyzed and its substantial interpretation is given. Based on received data, recommendations are issued to a pharmaceutical company PR-strategy development aimed to each consumer target group as to confidence generation to manufactured medicines. The received results allow to build PR-activities aimed to effective formation of customer positive attitude and loyalty.